2011
DOI: 10.1177/0022034511402994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling Mechanisms of the Periopathogen, Treponema denticola

Abstract: In the healthy subgingiva, oral treponemes account for a small percentage of the total bacteria. However, in diseased periodontal pockets, treponemes thrive and become a dominant component of the bacterial population. Oral treponemes are uniquely adept at capitalizing on the environmental conditions that develop with periodontal disease. The molecular basis of adaptive responses of oral treponemes is just beginning to be investigated and defined. The completion of several treponeme genome sequences and the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Not surprisingly also, many DFI organisms can degrade high molecular weight organic matter, as mentioned above. Most Spirochetes and Apicomplexa are pathogens that must scavenge available nutrients in their niche tissues; for instance, T. denticola, a periodontal pathogen, thrives in the anaerobic conditions under the gum (Frederick et al 2011;Sela 2001). Capnocytophaga spp.…”
Section: Dfi Genes Occur In Select Microorganisms Onlymentioning
confidence: 99%
“…Not surprisingly also, many DFI organisms can degrade high molecular weight organic matter, as mentioned above. Most Spirochetes and Apicomplexa are pathogens that must scavenge available nutrients in their niche tissues; for instance, T. denticola, a periodontal pathogen, thrives in the anaerobic conditions under the gum (Frederick et al 2011;Sela 2001). Capnocytophaga spp.…”
Section: Dfi Genes Occur In Select Microorganisms Onlymentioning
confidence: 99%
“…However, the regulatory pathways and effectors that control adaptive responses are relatively unknown. Frederick et al (2011) sought to gain additional insight into the potential regulatory networks involved in environmental adaptation through a bioinformatics-based assessment of the T. denticola 35405 genome. In bacteria, two component regulatory (TCR) systems are key players in adaptive responses.…”
Section: Two Component Regulatory Systems and Adaptive Responses Of Tmentioning
confidence: 99%
“…Frederick et al recently predicted that TDE0214 is an effector protein of c-di-GMP (41). Along with this prediction, sequence alignment with the Vibrio cholerae PlzD (17), P. aeruginosa PilZ (23), and Borrelia burgdorferi PlzA (18,28) proteins revealed that TDE0214 harbors a PilZ-like domain with two signature motifs, RXXXR and DXSXXG (Fig.…”
Section: Tde0214 Is a C-di-gmp Binding Proteinmentioning
confidence: 83%
“…The T. denticola ATCC 35405 strain was recently sequenced (40). Its genome encodes five proteins (TDE0125, TDE1685, TDE2725, TDE2580, and TDE2582) that harbor a well-conserved GGD/EEF domain, two proteins (TDE0128 and TDE2075) with an EAL domain, four proteins (TDE1256, TDE1467, TDE2302, and TDE2659) with an HD-GYP domain, and two putative c-di-GMP binding proteins (TDE0214 and TDE1318) (41), suggesting the existence of c-di-GMP signal-ing pathways in T. denticola. The work reported here attempts to uncover the potential roles of c-di-GMP-mediated regulatory networks in T. denticola via study of TDE0214, a putative PilZ-containing protein.…”
mentioning
confidence: 99%